Malaria knowledge and experiences with community health workers among recently pregnant women in Malawi - Ashley Malpass; Jobiba Chinkhumba; Elizabeth Davlantes; John Munthali; Katherine Wright; Kathryn Ramsey; Peter Troell; Michael Kayange; Fannie Kachale; Don P. Mathanga; Dziko Chatata; Julie R. Gutman (Malaria Journal, 2020)
Abstract Background The World Health Organization recommends three or more doses of intermittent preventive treatment in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) to mitigate the negative effects of malaria in pregnancy (MIP). Many pregnant women in Malawi are not receiving the recommended number of doses. Community delivery of IPTp (cIPTp) is being piloted as a new approach to increase coverage. This survey assessed recently pregnant women’s knowledge of MIP and their experiences with community health workers (CHWs) prior to implementing cIPTp. Methods Data were collected via a household survey in Ntcheu and Nkhata Bay Districts, Malawi, from women aged 16–49 years who had a pregnancy resulting in a live birth in the previous 12 months. Survey questions were primarily open response and utilized review of the woman’s health passport whenever possible. Analyses accounted for selection weighting and clustering at the health facility level and explored heterogeneity between districts. Results A total of 370 women were interviewed. Women in both districts found their community health workers (CHWs) to be helpful (77.9%), but only 35.7% spoke with a CHW about antenatal care and 25.8% received assistance for malaria during their most recent pregnancy. A greater proportion of women in Nkhata Bay than Ntcheu reported receiving assistance with malaria from a CHW (42.7% vs 21.9%, p = 0.01); women in Nkhata Bay were more likely to cite IPTp-SP as a way to prevent MIP (41.0% vs 24.8%, p = 0.02) and were more likely to cite mosquito bites as the only way to spread malaria (70.6% vs 62.0% p = 0.03). Women in Nkhata Bay were more likely to receive 3 + doses of IPTp-SP (IPTp3) (59.2% vs 41.8%, p = 0.0002). Adequate knowledge was associated with increased odds of receiving IPTp3, although not statistically significantly so (adjusted odds ratio = 1.50, 95% confidence interval 0.97–2.32, p-value 0.066). Conclusions Women reported positive experiences with CHWs, but there was not a focus on MIP. Women in Nkhata Bay were more likely to be assisted by a CHW, had better knowledge, and were more likely to receive IPTp3+ . Increasing CHW focus on the dangers of MIP and implementing cIPTp has the potential to increase IPTp coverage.